GAMBARAN TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG PERSONAL HYGIENE DAN KEJADIAN KEPUTIHAN - Pondaang, Mytha Febriany; Januar Dwi Christy (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2023)
Vaginal discharge is fluid or secretions that come out of the vagina. Vaginal discharge can be physiological or normal, or pathological as a sign of a disease. According to Prabawati (2019) in Indonesia, 90% of women have experienced vaginal discharge, and most of them are experienced by adolescent girls. Therefore, this study aims to describe the level of personal hygiene knowledge on the incidence of vaginal discharge in grade X of adolescent girls at SMAN 4 Surabaya. The method used descriptive research, where the population is all adolescent girls grade X SMAN 4 Surabaya. The sampling technique was carried out by non-probability sampling with a saturated sample technique of 169 adolescent girls in class X. The variables in this study were the knowledge of adolescent girls about personal hygiene and the incidence of vaginal discharge obtained through questionnaires. Data analysis uses simple descriptive univariate analysis in the form of percentages. The results found that the majority of adolescent girls who experienced vaginal discharge had less knowledge about personal hygiene, namely, as many as 49 female students (85.96%) compared to adolescent girls who had good knowledge who experienced vaginal discharge, as many as 41 female students (60.29%). It can be concluded that there are still many class X girls at SMAN 4 Surabaya who experience vaginal discharge and have less knowledge about personal hygiene. To overcome this, many adolescent girls increase their knowledge about personal hygiene by providing counseling on clean and healthy living behavior (PHBS) in collaboration with educational institutions (schools).